ANALISIS TEKSTUAL NILAI KEBHINEKAAN DALAM MATERI PENDIDIKAN AGAMA KATOLIK DAN BUDI PEKERTI TINGKAT SEKOLAH MENENGAH ATAS UNTUK MENDUKUNG MODERASI BERAGAMA - & Vinsensius Nase, Keristian Dahurandi, Ernestina Daimun (STIPAS St. Sirilus Ruteng, 2023)
This article contains an analysis of the internalization of the value of diversity in Catholic Religious Education (PAK) for High School (SMA) learning materials to support the implementation of religious moderation efforts in schools. Religious moderation aims to integrate diversity which tends to be a central issue for the life of diversity in Indonesia. Religious issues tend to be sensitive, so the issue of religious freedom is still a question because religious radicalism is prone to occur. One of the causes of radicalism is extreme doctrination that strays far from the authentic meaning of religion. Apart from that, this radicalism is also caused by a lack of understanding of the multicultural concept and Bhinneka Tunggal Ika as a typical model of Indonesian multiculturalism. So to answer this problem, this paper examines the material, basic competencies, indicators of achieving PAK and Budi Pekerti learning competencies at the high school level. The results of the study show that only 49.72% of PAK and Budi Pekerti learning materials at the high school level contain diversity values. These findings show that technically, PAK and Budi Pekerti learning materials can be the cause of intolerant attitudes towards diversity. These findings can be a reference so that the internalization of the value of diversity in PAK and Budi Pekerti learning materials in schools needs to be considered in a balanced manner so that religious moderation can run optimally in Indonesia. Artikel ini berisi analisis internalisasi nilai kebhinekaan dalam materi pembelajaran Pendidikan Agama Katolik (PAK) Sekolah Menengah Atas (SMA) untuk mendukung terlaksananya upaya moderasi beragama di sekolah. Moderasi beragama bertujuan untuk mengintegrasikan keberagaman yang cenderung menjadi persoalan sentral bagi kehidupan kebhinekaan di Indonesia. Masalah-masalah agama cenderung sensitive, sehingga persoalan tentang kebebasan beragama masih menjadi pertanyaan karena radikalisme agama rentan terjadi. Salah satu sebab terjadinya radikalisme adalah doktrinasi ekstrem yang melenceng jauh dari makna otentik agama. Selain itu, radikalisme ini juga disebabkan kurangnya pemahaman tentang konsep multikultural dan Bhineka Tunggal Ika sebagai model khas multikulturalisme Indonesia. Maka untuk menjawab permasalahan tersebut, tulisan ini mengkaji tentang materi, kompetensi dasar, indikator pencapaian kompetensi pembelajaran PAK dan Budi Pekerti tingkat SMA. Hasil kajian menunjukkan bahwa hanya 49,72% materi pembelajaran PAK dan Budi Pekerti pada tingkat SMA yang memuat nilai kebhinekaan. Temuan ini menunjukkan bahwa secara tekstual, materi pembelajaran PAK dan Budi Pekerti dapat menjadi penyebab adanya sikap intoleran terhadap kebhinekaan. Temuan ini dapat menjadi rujukan agar internalisasi nilai kebhinekaan dalam materi pembelajaran PAK di sekolah perlu diperhatikan secara seimbang agar moderasi beragama berjalan secara maksimal di negara Kesatuan Republik Indonesia.